Pengembangan Sistem Peningkatan Motivasi, Komitmen dan Moralitas SDM di Lembaga Pendidikan Islam - Fauzan Adhim (STAIFAS-Press, 2018)
Its role determines the succession of the process of administering education. Ignoring human resources is the same as making a death hole for educational institutions. It is on the basis of the urgency of human Resources that the concept and model of human Resources management emerge in educational institutions. In general, the concept can be categorized into two models. [1] human Resources as a person who has motivation, commitment and morality. Thus, the management efforts carried out must be in order to improve the overall personality above; [2] human Resources as a unified system in educational institutions. The efforts made by the manager are to build a system and a model that becomes a reference and performance guide for all human Resources. human Resources motivation is related to psychological drives that are influenced by two factors, namely internal and external, or intrinsic and extrinsic. Internal factors can be influenced by basic human needs as Maslow's theory. human Resources commitment is related to identification of feelings, participation and loyalty to the organization. So if you want to know someone's commitment then you can see their loyalty to the organization.